Conceptual bases of educational inclusion - López Azuaga, Rafael (Avances en Supervisión Educativa, 2011)
Currently developing the system of "inclusive education" to meet the special educational needs of students in regular schools. However, do not get the best students who have a disability, developmental disorder or any other specific need support to develop their skills and aspire to equal opportunities. Therefore, in this article, we present the updated conceptual model of "inclusive education", to today, guidance with some guidelines to carry it out.
Keywords: inclusion; special needs education support; cooperative learning; collaboration